A Founder Mutation in EHD1 Presents with Tubular Proteinuria and Deafness. Issue 4 (April 2022) - Issler, Naomi; Afonso, Sara; Weissman, Irith; Jordan, Katrin; Cebrian-Serrano, Alberto; Meindl, Katrin; Dahlke, Eileen; Tziridis, Konstantin; Yan, Guanhua; Robles-López, José M.; Tabernero, Lydia; Patel, Vaksha; et al.
Significance Statement: Renal tubular protein reabsorption has been of interest in the kidney community, and despite recognition of numerous associated inherited diseases, the detailed molecular basis remains poorly understood. We identified a missense mutation in EHD1 in six patients with tubular proteinuria and sensorineural hearing deficit, identifying the gene as a critical component of the renal protein reabsorption machinery and of inner ear function. EHD1, a key player in vesicular dynamics, has previously been associated with early ciliogenesis. However, no obvious defect of ciliogenesis was found in the kidneys of the patients nor in knockin and knockout mice. These data may contribute to a better understanding of the functional relevance of EHD1 in human tissues, particularly in the kidney and inner ear. Visual Abstract: Abstract : Background: The endocytic reabsorption of proteins in the proximal tubule requires a complex machinery and defects can lead to tubular proteinuria. The precise mechanisms of endocytosis and processing of receptors and cargo are incompletely understood. EHD1 belongs to a family of proteins presumably involved in the scission of intracellular vesicles and in ciliogenesis. However, the relevance of EHD1 in human tissues, in particular in the kidney, was unknown. Methods: Genetic techniques were used in patients with tubular proteinuria and deafness to identify the disease-causing gene. Diagnostic and functional studies were performed in patients and disease models to investigate the pathophysiology. Results: We identified six individuals (5–33 years) with proteinuria and a high-frequency hearing deficit associated with the homozygous missense variant c.1192C>T (p.R398W) in EHD1 . Proteinuria (0.7–2.1 g/d) consisted predominantly of low molecular weight proteins, reflecting impaired renal proximal tubular endocytosis of filtered proteins. Ehd1 knockout and Ehd1 R398W/R398W knockin mice also showed a high-frequency hearing deficit and impaired receptor-mediated endocytosis in proximal tubules, and a zebrafish model showed impaired ability to reabsorb low molecular weight dextran. Interestingly, ciliogenesis appeared unaffected in patients and mouse models. In silico structural analysis predicted a destabilizing effect of the R398W variant and possible inference with nucleotide binding leading to impaired EHD1 oligomerization and membrane remodeling ability. Conclusions: A homozygous missense variant of EHD1 causes a previously unrecognized autosomal recessive disorder characterized by sensorineural deafness and tubular proteinuria. Recessive EHD1 variants should be considered in individuals with hearing impairment, especially if tubular proteinuria is noted.